Turning corn silage analysis into economic value for the beef industry - Mitchell, Brook D. (Kansas State University, 2016)
The corn silage market is typically focused heavily on the dairy market and results for corn silage plots are dedicated to the dairy industry specifically to get to the overall answer of $ Milk/Acre. The beef cattle industry is more interested in pounds of beef that can be gained from corn silage. There are roughly 6.2 million acres of corn silage in the US. Within that 6 million acres, roughly half is fed to beef cattle, but the corn silage industry has not focused on this aspect of the market. Within Mycogen Seeds there has been an ever increasing demand to find a way to deliver the corn silage plot data in a useable format for beef producers. By delivering corn silage plot data to beef producers, Mycogen has aspirations of increasing it’s market share of the corn silage market in Kansas as well as across the US, while at the same time increasing the awareness of how quality of a corn silage hybrid can affect a producers operation. This thesis examines corn silage plot info sample analysis and specific feed analysis calculations. With these specific calculations, the corn silage plot will illustrate information in a form that beef producers will understand, $ Beef Produced/Acre. At the same time, this thesis will examine the industry wide concept that tonnage is the only component that is important when selecting a corn silage hybrid. Finally this thesis will examine at what point ($/bushel) in the corn grain market does it make sense to start looking at utilizing corn silage over dry rolled corn by comparing price per MegaCalorie of energy by utilizing 25 year historical corn grain prices and using the Purdue Method of determining the cost of corn silage on a per ton basis.
Keywords: Corn silage; Beef industry; Corn silage plot data